PEKERJAAN DAN AKTIVITAS FISIK YANG MEMPENGARUHI PERUBAHAN BERAT BADAN PADA IBU PENGGUNA ALAT KONTRASEPSI IMPLAN - Saleh, Ummi Kaltsum; Manalor, Loriana L; Ernita, Ernita (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
One of the Millennium Development Goals (MDGs) 2015 targets is to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), as well as improving maternal health. Maternal health is a very important component in reproductive health and in creating a healthy family. The purpose of this study was to analyze the effect of occupational factors and physical activity of mothers using implant contraceptive devices on weight changes at the oebobo health center Kupang City. This research method was analytical observational with cross-sectional design. The sample of this study was 70 respondents. The Effect of Work on Changes in the body weight gain of the non-worker respondents using implants were 25 people (35.7%), while the worker respondents were 11 people (15.7%). The results of this study indicate that non worker respondents, in this case housewives, experience weight gain. The Effect of Physical Activity on Changes in body weight gain of the respondents using implants with strenuous activities experienced weight gain as many as 13 people (18.6%), and respondents with lighter activities experienced more weight gain as many as 16 people (22.9%), while respondents with moderate activities most experienced weight gain as many as 7 people (10.0%). There is a relatively little work at home because there are auxiliary facilities that do their work, hence the activities carried out tend to not expend a lot of energy and the intake of nutrients that are put into the body is not balanced with the energy that is expended through the work done or expended through sweating or burning fat. This measurable physical activity is expected to help maintain physical fitness and help channel energy and burn fat to prevent obesity. There is no effect of work while there is an effect of physical activity on changes in body weight in implant users at the Fatululi Public Health Center in 2016.